Biology and ecology of sea catfish (Ariidae) of estuarine, lagoon and coastal ecosystems in West Africa. Issue 2 (27th April 2021) - Simier, Monique; Osse, Olaloudé Judicaël Franck; Sadio, Oumar; Ecoutin, Jean‐Marc
Abstract: The family Ariidae, sea catfish of the order Siluriformes, is widely distributed throughout the world, particularly in tropical and subtropical areas. The three species of Ariidae found on the coasts and estuaries of West Africa are the smoothmouth catfish Carlarius heudelotii (Valenciennes 1840), the rough‐head catfish Carlarius latiscutatus (Günther 1864) and the Guinean sea catfish Carlarius parkii (Günther 1864). They have been increasingly exploited by artisanal and industrial coastal fisheries in recent decades, but there is still little information available on their ecology and biology. The aim of this study was to deepen our knowledge of these three West African Ariidae species based on a dataset collected between 1980 and 2013 during experimental fishing programmes. They were carried out in Mauritania in the Banc d'Arguin National Park, in Senegal in the Sine Saloum estuary including the Bamboung Marine Protected Area (MPA), in The Gambia in the Gambia estuary, in Guinea‐Bissau in the Urok Islands MPA in the Bijagos archipelago, in Guinea in the Fatala estuary and Dangara inlet, and in Côte d'Ivoire in the Ebrié Lagoon. C. latiscutatus accounted for 65%, C. parkii for 29% and C. heudelotii for 6% of total number of Ariidae sampled. C. latiscutatus was abundant in the Sine Saloum and Gambia estuaries as well as in Guinea and Guinea‐Bissau and was the only species present in the Ebrié Lagoon. C. parkii was in the majority in Mauritania. The three species were recorded in a salinity range of 0 to 50, a temperature range of 19 to 34°C, in areas 1.7 to 15 m depth, and transparency ranging from 0.1 to 4 m (Secchi disk depth). C. heudelotii was present in less saline (25 vs . 32–34), less warm (27 vs . 29°C) and less transparent (0.8 m vs . 1.6 m) waters than the two other species. The maximum sizes (453 mm, 614 mm and 525 mm for, respectively, C. heudelotii, C. latiscutatus and C. parkii ) were comparable to those recorded at sea. Length–weight relationships calculated for each species showed b coefficients greater than 3. Sex ratios were always in favour of females. The number of mature individuals and their smallest size at maturity were calculated per species, sex and study area. A size of 27–28 cm at first maturity was estimated for females of C. latiscutatus . A few dozen records made it possible to describe fecundity and cases of oral incubation by females. The diet of the three species was composed of crustaceans, fish and molluscs, confirming their classification as generalist predators. Thanks to their high environmental tolerance, these sea catfish populations are able to occupy both the continental shelf and adjacent estuaries throughout their life cycle, with the exception of spawning, which generally takes place at sea.